THE ROLE OF RELIGIOUS VALUES IN PROTECTING YOUTH FROM VARIOUS IDEOLOGICAL THREATS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The article conditionally classifies threats into economic, social, political, natural-climatic, ecological, demographic, ideological, and military categories, and considers it appropriate to define all of them under the general concept of “social threats.” This is because all these threats are fundamentally based on social relations and processes primarily connected with human activity.